PENANGANAN PERKARA PRE-NOTIFICATION OLEH KPPU DALAM KERANGKA HUKUM PERSAINGAN USAHA DI INDONESIA - Wizna Gania Balqis (Jurnal Yustisiabel, 2020)
KPPU is an independent commission established by law, which in dealing, deciding or investigating a matter cannot be affected by any party, neither the government nor the other party having the Conflik of Interest. Normative legal research will examine the problem of the acquisition process (acquisitions) related to the ruling KPPU number 05/KPPU-M/2017 and about the function and role of KPPU in the law enforcement of business competition against the handling of pre-notification matters. This research shows that the acquisition process of PT. Iforte Solusi Infotek by PT. Profesional Telekomunikasi has violated article 29 of Law No. 5 of 1999 and article 5 of government Regulation number 57 of 2010. Then KPPU authorized in conducting checks on business actors, witnesses, and other parties because of the report from the community or reports from businesses that are harmed by other businesses. One of them is for handling Pre-Notification matters.